If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(z + -1x) = 5x + -1(3x + 2) Reorder the terms: 2(-1x + z) = 5x + -1(3x + 2) (-1x * 2 + z * 2) = 5x + -1(3x + 2) (-2x + 2z) = 5x + -1(3x + 2) Reorder the terms: -2x + 2z = 5x + -1(2 + 3x) -2x + 2z = 5x + (2 * -1 + 3x * -1) -2x + 2z = 5x + (-2 + -3x) Reorder the terms: -2x + 2z = -2 + 5x + -3x Combine like terms: 5x + -3x = 2x -2x + 2z = -2 + 2x Solving -2x + 2z = -2 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2x + -2x + 2z = -2 + 2x + -2x Combine like terms: -2x + -2x = -4x -4x + 2z = -2 + 2x + -2x Combine like terms: 2x + -2x = 0 -4x + 2z = -2 + 0 -4x + 2z = -2 Add '-2z' to each side of the equation. -4x + 2z + -2z = -2 + -2z Combine like terms: 2z + -2z = 0 -4x + 0 = -2 + -2z -4x = -2 + -2z Divide each side by '-4'. x = 0.5 + 0.5z Simplifying x = 0.5 + 0.5z
| 25/57=849/5x | | w^8+11w^4+10= | | 7x+5y=9 | | y=2/5-2 | | 8b+11-3b=2b-3+5 | | 3/4x-7=17 | | 4x^2+17=5 | | (45-27)n= | | x+1/3+x+2/7=2 | | 14-3(5t-12)=1-(29t+1) | | 3x-(2x-7)=3(1+x) | | S=r | | x^2+2xy+y^2=x^2+y^2 | | 3a+6-2a+9+5a= | | 9k+3=8k+19 | | x^2+2xy+y^2=x+y^2 | | 1/6(2x-9)=7 | | 7-2i= | | 31=-42+x | | f(x)=3x+7 | | 3(x-2)+2(x+1)=-19 | | 5m-24=36 | | 3x+4x+(4x+24)+x=360 | | 5x+8y=480 | | 3x+10=6x-4 | | 6(x-3)-10=32 | | 4x+3(x+2)=58 | | 4x+3(x+2)=54 | | 7+m+(6m-3)= | | 15-3x-1=12 | | 7+m+9(6m-3)= | | 8x+14=8x+14 |